Señales EOG: una revisión sobre procesamiento y aplicaciones - David Escobar-Valencia; Fernando Jesús Regino-Ubarnes; Diana Yamileth Velásquez-Maldonado (Mundo Fesc)
This paper presents a review of electrooculography signal processing and applications. First, it presents a general framework for using these signals. It then describes cutting-edge research on systems based on electrooculography signals. The objective of this review is to identify advances in systems based on these signals for future technological developments.